Political-institutional components: relevant to local development. The case of rururban communities of León, Guanajuato, México - Suárez-Paniagua, Suana; García-Vázquez, Arlene Iskra (Advances in Social Sciences Research Journal, 2017)
This paper examines the main changes that have occurred in the political-institutional components (organization and function) of rural communities, identifying whether they respond to the new socio-spatial organization and whether they contribute to local development. The analysis of empirical information is based on the approaches of territorial development and the process of rururbanization. It was found that these communities have experimented economic, social and political changes which have disappeared their old forms of social and political organization, of rural origin leaving insufficient political representation to attend to their problems and to detonate processes of local development.